2011
DOI: 10.1590/s1677-54492011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Implementação financeira e o impacto do mutirão de cirurgias de varizes, após a criação do Fundo de Ações Estratégias e Compensação (FAEC)

Abstract: Background: In spite of the fact that the number of surgeries presented by the elective surgery task force did not entirely reflect the reality, it is possible to declare that the financial implementation of the Brazilian Ministry of Health has been significative, as well as the increasing number of varicose vein surgeries, especially after the creation of the Strategic Actions and Compensation Fund (FAEC). Objective: To evaluate the application of financial investment in the Ministry of Health campaign for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…As for the surgical aspect, the authors highlighted that the lack of data about the surgical method used 12,13,25,30,51 represented a bias in their analyses. Also, information about the postoperative period of patients, such as the need for reintervention, readmission, and the rate of postoperative complications are also not recorded on the platform 9 , 12 , 13 , 19 , 23 , 27 , 32 , 34 , 35 , 47 , 51 , 53 . Information on the average length of stay of the patient in each hospital is also not available 40 .…”
Section: Resultsmentioning
confidence: 99%
“…As for the surgical aspect, the authors highlighted that the lack of data about the surgical method used 12,13,25,30,51 represented a bias in their analyses. Also, information about the postoperative period of patients, such as the need for reintervention, readmission, and the rate of postoperative complications are also not recorded on the platform 9 , 12 , 13 , 19 , 23 , 27 , 32 , 34 , 35 , 47 , 51 , 53 . Information on the average length of stay of the patient in each hospital is also not available 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Souza et al 20 reported that surgical procedures to correct superficial venous insufficiency lead to improvements in deep vein system function, improving these patients' clinical status. The data collected for the present study revealed that half of the patients (50%) reported having undergone this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…As doenças venosas constituem a sétima causa mais frequente de doença crônica na espécie humana, no Brasil, estima-se que a insuficiência venosa crônica ocupava o 14º lugar entre as 50 principais doenças que causaram ausência ao trabalho, e o 32º lugar entre as doenças que levaram à aposentadoria por invalidez (FARIA et al, 2010;SOUZA et al, 2011;ARAUJO et al, 2013;NERI;FELIS;SANDIM, 2020) De 2008 a agosto de 2015, o Sistema Único de Saúde teve um dispêndio de 43 milhões de reais em tratamento de varizes dos membros inferiores com 654.478 internações. Do total de benefícios concedidos pela previdência no ano de 2013 a Insuficiência Venosa Crônica periférica (CID 10-I87.2) ocupou a 10ª posição do Os fatores de risco para o desenvolvimento de IVC são apontados, em vários estudos, como: a idade avançada é um fator de risco expressivo para prevalência e gravidade da insuficiência venosa crônica, etnia, estudos apontam a necessidade mais estudos para se determinar melhor o papel da etnia como fator de risco para doença venosa.…”
Section: Introductionunclassified